2012
DOI: 10.1159/000335956
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Use and Immunogenicity of Hepatitis B Virus Vaccine in Chronic Kidney Disease Patients: A Meta-Analysis

Abstract: <b><i>Background:</i></b> It is known that the immunogenicity of hepatitis B virus (HBV) vaccine is lower in uremic patients than healthy subjects. Numerous inherited or acquired factors have been implicated in this lowered response, and the high frequency of recombinant human erythropoietin use among patients on maintenance dialysis has been suggested to play a pivotal role. However, the impact of therapy with recombinant erythropoietin on the immune response to HBV vaccine in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 70 publications
1
7
0
2
Order By: Relevance
“…Oster et al also reported that EPO treatment is associated with an improved immune response to influenza vaccine in hematologic patients, with titers similar to those of healthy subjects, although they did not examine the renal function of the patients (63). However, a meta-analysis of 11 studies failed to detect any benefit of EPO treatment regarding the response to HBV vaccine (64). Therefore, the role of EPO treatment in improving the function of DCs and their responsiveness to HBV vaccine remains to be elucidated.…”
Section: Modulation Of DC Function In Patients With Esrdmentioning
confidence: 99%
“…Oster et al also reported that EPO treatment is associated with an improved immune response to influenza vaccine in hematologic patients, with titers similar to those of healthy subjects, although they did not examine the renal function of the patients (63). However, a meta-analysis of 11 studies failed to detect any benefit of EPO treatment regarding the response to HBV vaccine (64). Therefore, the role of EPO treatment in improving the function of DCs and their responsiveness to HBV vaccine remains to be elucidated.…”
Section: Modulation Of DC Function In Patients With Esrdmentioning
confidence: 99%
“…It seems to be partly due to poor nutrition status and inflammation in these individuals (22). However, Fabrizi and his colleagues found that EPO injection has no effects on the HBV vaccination in patients who undergo HD (14). …”
Section: Special Groups Needs Special Attentionmentioning
confidence: 99%
“…However, clinical trials have also proposed several other factors having predictive values in this era; but due to the controversial evidence provided by different reports, systematic reviews and metaanalyses have been conducted to pool data of all the published trials to provide a thorough conclusion from the cumulative data. Most of the published systematic reviews on this subject have been performed by Fabrizi et al [31] investigating potential effects of a large number of factors on HBV vaccination in dialysis patients. For example they found no significant effects for using erythropoetin (Epo) [31] and some other adjuvants [32] on the immunogeneity of HB vaccination in kidney disease patients; while several other factors significantly associated with seroconversion have also been reported by the same authors that included use of levamisole [33] , granulocyte macrophage-colony stimulating factor [32] and thymopentin use [34] .…”
Section: Discussionmentioning
confidence: 99%